The real effects of money growth in dynamic general equilibrium - Liam Graham; Dennis J. Snower (European Central Bank (ECB), 2004)
We analyse the effects of money growth within a standard New Keynesian framework and show that the interaction between staggered nominal contracts and money growth leads to a long-run trade-off between output and money growth. We explore the microeconomic mechanisms that lead to this trade-off, and show that it remains even when the contract length is endogenised.
Keywords: E20; E40; E50; 330; inflation; nominal inertia; Phillips curve; Unemployment